Effectiveness of incentivised adherence and abstinence monitoring in buprenorphine maintenance: a pragmatic, randomised controlled trial. (28th January 2021) - Elarabi, Hesham Farouk; Shawky, Mansour; Mustafa, Nael; Radwan, Doaa; Elarasheed, Abuelgasim; Yousif Ali, Ahmed; Osman, Mona; Kashmar, Ahmed; Al Kathiri, Helal; Gawad, Tarek; Kodera, Ayman; Al Jneibi, Mohammed; et al.
ABSTRACT: Background and Aim: Buprenorphine (BUP) maintenance treatment for opioid use disorder (OUD) begins with supervised daily dosing. We estimated the clinical effectiveness of a novel incentivised medication adherence and abstinence monitoring protocol in BUP maintenance to enable contingent access to increasing take‐home medication supplies. Design: Two‐arm, single‐centre, pragmatic, randomised controlled trial of outpatient BUP maintenance, with during‐treatment follow‐ups at 4 weeks, 8 weeks, 12 weeks and 16 weeks. Setting: Inpatient and outpatient addictions treatment centre in the United Arab Emirates. Participants: Adults with OUD, voluntarily seeking treatment. Interventions: The experimental condition was 16 weeks BUP maintenance with incentivised adherence and abstinence monitoring (I‐AAM) giving contingent access to 7‐day, then 14‐day, then 21‐day and 28‐day medication supply. The control, treatment‐as‐usual (TAU) was 16 weeks BUP maintenance, with contingent access to 7‐day then 14‐day supply. Measurements: The primary outcome was number of negative urine drug screens (UDS) for opioids, with non‐attendance or otherwise missed UDS, imputed as positive for opioids. The secondary outcome was retention in treatment (continuous enrolment to the 16‐week endpoint). Findings: Of 182 patients screened, 171 were enrolled and 141 were randomly assigned to I‐AAM (70 [49.6%]) and to TAU (71 [50.4%]. Follow‐up rates at 4 weeks, 8 weeks, 12 weeks and 16 weeks were 91.4%, 85.7%, 71.0%, 60.0% respectively in I‐AAM and 84.5%, 83.1%, 69.0%, 56.3% in TAU. By intention‐to‐treat, the absolute difference in percentage negative UDS for opioids was 76.7% (SD = 25.0%) in I‐AAM versus 63.5% (SD = 34.7%) in TAU (mean difference = 13.3%; 95% CI = 3.2%–23.3%; Cohen's d = 0.44; 95% CI = 0.10–0.87). In I‐AAM, 40 participants (57.1%) were retained versus 33 (46.4%) in TAU (odds ratio = 1.54; 95% CI = 0.79–2.98). Conclusions: Buprenorphine maintenance with incentivised therapeutic drug monitoring to enable contingent access to increasing take‐home medication supplies increased abstinence from opioids compared with buprenorphine maintenance treatment‐as‐usual, but it did not appear to increase treatment retention.